HUBUNGAN PENGGUNAAN MEDIA PEMBELAJARAN TUTORIAL INTERAKTIF DAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR SISWA MATA PELAJARAN MENGGAMBAR DENGAN PERANGKAT LUNAK (Studi Kasus di SMK Negeri 1 Sintang) - Anwar, Rosihan (LPPM, Universitas Negeri Jakarta, 2020)
This research aimed to know the correlation between the of tutorial interactive learning instructional media and learning motivation toward learning results, Indonesian history subject, of senior high students at SMK Negeri 1 Sintang. As the result, it showed that instructional media and learning motivation positively influenced students learning result. These results indicate that the use of interactive tutorial learning media can be used to improve student learning outcomes. Keywords: instructional media, learning motivation, learning results